The intertemporal approach to the current account: evidence from Argentina - Moccero, Diego Nicolás (2006)
In this paper, an intertemporal model is used to analyze the current account and test whether it accounts for the evolution of the Argentinean current account over the period extending from 1855 to 2002. The intertemporal model presented here takes into account several sources of external shocks for small economies such as a change of the real interest rate and the real exchange rate. Evidence shows that the intertemporal model does not pass the statistical tests and does not explain the Argentinean experience. More specifically, if the Argentinean current account was to behave as the model predicts, one would observe the opposite movement to that observed for the actual current account. Our main conjecture about the weak performance of the model is related to i) the fact that one of its most important assumption is violated for some part of the period under consideration (1931-1989); and ii) that the balance of payments crises and stop and go cycles may have altered the relation between the variables suggested by the model. To cope with this problem, we have estimated a model for the period 1885-1930 (a period with relatively high capital mobility and with neither currency crises nor stop and go cycles) and found some evidence in favour of this result. A general conclusion to be drawn is that, in contrast to other Latin American countries, an intertemporal current account model can not appropriately account for the dynamics of the current account of Argentina, even thought there is some evidence in favour of the model for the period 1885-1930.